2015
DOI: 10.1016/j.infbeh.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Associations between infant temperament, maternal stress, and infants’ sleep across the first year of life

Abstract: Effects of temperament and maternal stress on infant sleep behaviors were explored longitudinally. Negative temperament was associated with sleep problems, and with longer sleep latency and night wakefulness, whereas maternal stress was associated with day sleep duration, suggesting infant and maternal characteristics affect sleep differentially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 36 publications
4
25
0
1
Order By: Relevance
“…The current sample was drawn from a larger sample of 102 infants participating in a longitudinal study starting at 1 month through 24 months (Reeb-Sutherland et al, 2011; Reeb-Sutherland, Levitt, & Fox, 2012; Sorondo & Reeb-Sutherland, 2015; Yoo & Reeb-Sutherland, 2013). Families were recruited from counties surrounding a large mid-Atlantic university.…”
Section: Methodsmentioning
confidence: 99%
“…The current sample was drawn from a larger sample of 102 infants participating in a longitudinal study starting at 1 month through 24 months (Reeb-Sutherland et al, 2011; Reeb-Sutherland, Levitt, & Fox, 2012; Sorondo & Reeb-Sutherland, 2015; Yoo & Reeb-Sutherland, 2013). Families were recruited from counties surrounding a large mid-Atlantic university.…”
Section: Methodsmentioning
confidence: 99%
“…Parental mental health, especially maternal depression and fatigue and family dysfunction and stress have been associated with shorter sleep duration (day, night and 24-hour period) and longest sleep period (night), and more night wakings and WASO (Armitage et al, 2009;Baird et al, 2009;Brand et al, 2014;Dennis & Ross, 2005;Goldberg et al, 2013;Gress-Smith et al, 2012;Hughes et al, 2015;Karraker & Young, 2007;Loutzenhiser et al, 2015;Mao et al, 2011;Nevarez et al, 2010;O'Connor et al, 2007;Piteo et al, 2013;Saenz et al, 2015;Sinai & Tikotzky, 2012;Sorondo & Reeb-Sutherland, 2015;Warren et al, 2006). Depressed mothers may be less able to deal with family actives, namely infant sleep-wake behaviour (Piteo et al, 2013).…”
Section: Factors Positively and Negatively Associated With Sleep-wakementioning
confidence: 99%
“…Infant sleep quality and development can be modulated by a number of biopsychosocial factors [23]. These factors include inherited child's characteristics, such as temperament [24] or chronotype [19], perinatal characteristics such as season of birth [25] or photoperiod [26], and environmental characteristics such as parental stress [27]. Following this line of research, our recent study reported that some maternal risk factors during pregnancy are related to infants' sleep difficulties at three months of age [28].…”
Section: Introductionmentioning
confidence: 97%